Reconstruction of the Hip in Multiple Hereditary Exostoses - Dong Hoon Lee; Dror Paley (MDPI AG, 2021)
The hip joint involvement in multiple hereditary exostoses (MHE) occurs in 30-90%, causing pain and limitation of motion by femoroacetabular impingement, coxa valga, acetabular dysplasia, hip joint subluxation, and osteoarthritis. The purpose of this study was to investigate the clinical and radiographic outcomes of ten hips in seven patients treated by surgical dislocation and corrective osteotomies between 2004 and 2009. Surgical dislocation and excision of the osteochondromas and varus intertrochanteric osteotomies were performed in all cases when the neck-shaft angle was > 150°. Common sites of osteochondromas were medial, posterior, and anterior neck of the femur. Neck-shaft angle of the femur was improved from a mean of 157° to 139°, postoperatively. On an average, the center-edge angle improved from 20° to 30° postoperatively. We believe that Ganz's safe surgical dislocation technique is the preferred treatment of MHE. This safeguards the circulation of the femoral head and the osteochondromas can be resected under direct vision. It can be combined with additional corrective osteotomies because the hip affected by MHE is frequently associated with dysplastic changes which can result in premature osteoarthritis.